ANALISIS LAJU DEFORMASI PAHAT CARBIDE PADA SIMULASI PEMBUBUTAN BAJA ST41 DENGAN MESIN BUBUT KONVENSIONAL MENGGUNAKAN SOFTWARE ANSYS: Analysis of Carbide Tool Deformation Rate in Simulation of ST41 Steel Turning with Conventional Lathe using ANSYS Software - Ulin Nuha; Golwa, Gian Villany (Jurnal Konversi Energi dan Manufaktur, 2024)
In the machining process, knowledge of the tool and workpiece is required to achieve maximum results between quality and productivity. Tool wear parameters are very important to know because the process of changing or sharpening the tool can be predicted. One thing that influences the tool wear rate is the friction force between the tool and the workpiece. This frictional force will produce vibrations and heat energy, causing the chisel grains to erode so that they will experience wear within certain standards. This research aims to analyze the wear value of carbide-type tool edges in the ST41 material turning process based on the friction force that occurs between the tool and the workpiece. Then, from the wear value, the recommended cutting speed is. The method used is simulation-based research using ANSYS software, especially ANSYS Mechanical, by entering predetermined parameters, including diameter and spindle rotation. From the simulation results, the total deformation of workpieces with diameters of 25 mm, 35 mm and 45 mm is 0.363 μm, 0.155 μm and 0.152 μm, respectively. It can be concluded from the simulation results that the largest total deformation is at a diameter of 25 mm.